2014
DOI: 10.1002/dev.21236
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent latent inhibition in preweanling rats

Abstract: Preexposure to a conditioned stimulus (CS) usually weakens conditioning, an effect known as latent inhibition. Similar to other learning interference effects, latent inhibition has been characterized as context-dependent, which means that the magnitude of this effect can be attenuated by changing the context between the different phases of the procedure (e.g., preexposure and conditioning). Latent inhibition has been found with a variety of procedures in infant rats, but the few studies that examined the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
3
4
0
2
Order By: Relevance
“…Lesioning the model did not affect the output CR of the second phase after the pre-exposure at the beginning, as shown in Figure 23 . All of these results were confirmed experimentally by [ 58 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 73%
“…Lesioning the model did not affect the output CR of the second phase after the pre-exposure at the beginning, as shown in Figure 23 . All of these results were confirmed experimentally by [ 58 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 73%
“…In agreement with these results, some studies have found contextdependent interference learning in 23-day-old rats, but not in younger pre-weanlings (around PD 17), leading to the conclusion that the context does not influence interference learning during infancy (Kim and Richardson, 2010). However, other studies have recently reported clear evidences of context-dependent interference effects (for example, Revillo et al, 2013, Revillo et al, 2014, context learning (Ramsaran, Westbrook and Stanton, 2016) and Pavlovian contextual conditioning in pre-weanling rats (for example, Pugh and Rudy, 1996, Brasser and Spear, 1998, Park, Ganella and Kim, 2017Pisano et al, 2012). In fact, under particular conditions, contextual memory is even greater in infants than in adult rats (Brasser and Spear, 2004).…”
Section: Introductionsupporting
confidence: 60%
“…Subtle changes in task parameters can lead to important differences in performance, particularly at early stages of development during which rapid maturational changes occur. For instance, the sensory content of the context seems to be critical for some context effects during infancy, facilitating not only direct context conditioning (Brasser & Spear, 2004;Pugh & Rudy, 1996), but also interference effects (Revillo, Gaztanaga, et al, 2014, Revillo, Trebucq, et al, 2016. Interestingly, this and other studies demonstrating ABArenewal in preweaning rats included salient odors in the testing context (Revillo, Molina, et al, 2013, Revillo, Castelló et al, 2014, Revillo, Cotella, et al, 2015.…”
Section: Discussionmentioning
confidence: 75%